Surface ablation properties and morphology evolution of K24 nickel based superalloy with femtosecond laser percussion drilling. (March 2019) - Li, Qiang; Yang, Lijun; Hou, Chaojian; Adeyemi, Oluwaseun; Chen, Chaoyi; Wang, Yang
..Highlights: Morphology evolution of holes of K24 superalloy with femtosecond laser drilling is deeply investigated at different fluences. Increase of pulses number doesn't influence the change of entrance diameter of holes drilled at high fluences ranges. The increase of the hole diameter around entrance regions is influenced by the laser-induced plasma plume. Ablation mechanism of K24 superalloy with femtosecond laser drilling is elaborated discussed at different fluence and pulses number. Abstract: Due to the features of ultrashort pulse width and ultrahigh peak power, femtosecond laser is one of the most suitable methods for the fabrication of micro-scale structures. K24 superalloy, as a novel cast Ni-based alloy, is of great interest in the field of modern aviation engine manufacture owing to its high strength and strong anticorrosion ability. Thus, the processing quality of K24 superalloy is a key factor for the safety of aviation engine. In this paper, the investigation about surface morphology of K24 nickel based superalloy under femtosecond laser percussion drilling is carried out based on the effect of incident laser fluences and pulses number on the ablation process. The results show that the formation of surface morphology on the drilling process depends on different laser parameters. Upon the irradiation of low fluences (1–10 J/cm 2 ), laser-induced periodical surface structures (LIPSSs) occur at the region of laser irradiation. By contrast, the holes with high aspect ratio larger than ∼10:1 are attained under high fluences (121–605 J/cm 2 ). More important, the hole walls exhibits smooth surface at upper region and the capillary at bottom region, resulting from re-ablation of laser-induced plasma and inhomogeneous pressure gradient at the inner part of holes. The whole investigation has an important practical significance for femtosecond laser drilling on the superalloy.